The direct oxidative diene cyclization and related reactions in natural product synthesis - Adrian, Juliane; Gross, Leona J.; Stark, Christian B. W. (Beilstein Journal of Organic Chemistry, 2016)
The direct oxidative cyclization of 1,5-dienes is a valuable synthetic method for the (dia)stereoselective preparation of substituted tetrahydrofurans. Closely related reactions start from 5,6-dihydroxy or 5-hydroxyalkenes to generate similar products in a mechanistically analogous manner. After a brief overview on the history of this group of transformations and a survey on mechanistic and stereochemical aspects, this review article provides a summary on applications in natural product synthesis. Moreover, current limitations and future directions in this area of chemistry are discussed.
Keywords: asymmetric synthesis; natural products; oxidation catalysis; tetrahydrofurans; total synthesis